An analysis of how AIS aid in improving financial performance and decision making - Masukume, Abigail Kudzai (Midlands State University, 2017)
Accounting information system has aided the performance and decision making of many organizations since the introduction of information technology. The research mainly focused on finding out if accounting information system has also aided the performance of delta beverages Kadoma. The research advocates that the use of accounting information system aid performance measures and decision making. The descriptive research method was used on a census to obtain evidence from the organization under study. The research was carried out though the issuing questionnaires and conducting interviews. Findings from the research indicated that the use of accounting information system has aided the performance measures and decision making at Delta Beverages Kadoma, but however the use of AIS still needs to be improved on as management can now make real time decisions. It was also found that there is still need to improve on the security for both the system and the hardware. The findings from the research were also used to give recommendations that could be implemented by Delta Beverages which include conducting security campaigns and awareness’s so as to ensure security for both the hardware and software.